Effects of aging on organic aerosol from open biomass burning smoke in aircraft and laboratory studies - M. J. Cubison; A. M. Ortega; P. L. Hayes; D. K. Farmer; D. Day; M. J. Lechner; W. H. Brune; E. Apel; G. S. Diskin; J. A. Fisher; H. E. Fuelberg; A. Hecobian; et al. (Atmospheric Chemistry and Physics, 2011)
Biomass burning (BB) is a large source of primary and secondary organic aerosols (POA and SOA). This study addresses the physical and chemical evolution of BB organic aerosols. Firstly, the evolution and lifetime of BB POA and SOA signatures observed with the Aerodyne Aerosol Mass Spectrometer are investigated, focusing on measurements at high-latitudes acquired during the 2008 NASA ARCTAS mission, in comparison to data from other field studies and from laboratory aging experiments. The parameter f60, the ratio of the integrated signal at m/z 60 to the total signal in the organic component mass spectrum, is used as a marker to study the rate of oxidation and fate of the BB POA. A background level of f60~0.3% ± 0.06% for SOA-dominated ambient OA is shown to be an appropriate background level for this tracer. Using also f44 as a tracer for SOA and aged POA and a surrogate of organic O:C, a novel graphical method is presented to characterise the aging of BB plumes. Similar trends of decreasing f60 and increasing f44 with aging are observed in most field and lab studies. At least some very aged BB plumes retain a clear f60 signature. A statistically significant difference in f60 between highly-oxygenated OA of BB and non-BB origin is observed using this tracer, consistent with a substantial contribution of BBOA to the springtime Arctic aerosol burden in 2008. Secondly, a summary is presented of results on the net enhancement of OA with aging of BB plumes, which shows large variability. The estimates of net OA gain range from ΔOA/ΔCO(mass) = −0.01 to ~0.05, with a mean ΔOA/POA ~19%. With these ratios and global inventories of BB CO and POA a global net OA source due to aging of BB plumes of ~8 ± 7 Tg OA yr−1 is estimated, of the order of 5 % of recent total OA source estimates. Further field data following BB plume advection should be a focus of future research in order to better constrain this potentially important contribution to the OA burden.